Nd:YAG laser welding of Ti-27 at.% Nb shape memory alloys - Bahador, A.; Saud, S.N.; Hamzah, E.; Abubakar, T.; Yusof, F.; Ibrahim, M.K. (Springer Verlag (Germany), 2016)
A Nd:YAG laser welding technique with varying pulse widths was employed to weld Ti-27 at.% Nb shape memory alloy plates, and subsequent phase transformation characteristics and microhardness of welds were systematically investigated. From microstructure observation, it is apparent that weld seams contain a columnar growth with the low pulse and transferred into a combined growth of columnar and planar with the high pulse width. Moreover, grains in the weld zone exhibited a finer size when compared to the unwelded zone. A small amount of NbTi4 was also found in the welds. In the forward transformation, transformation temperatures did not exhibit peaks, indicating the same behaviour as the original TiNb alloy. Microhardness of the TiNb welds increased as the pulse width increased when compared to the original TiNb alloy. However, little reduction in hardness occurred after a pulse width of 5 ms.